Revision of Old World species of Setaria (Poaceae: Panicoideae: Paniceae) - Morrone, Osvaldo (2014)
Setaria (Poaceae: Panicoideae: Paniceae) in the Old World is revised, providing identification tools for a group that includes many important forage grasses and several widespread weeds. Setaria includes annual and perennial species of open and dry places, with membranous-ciliate ligules, lanceolate to filiform leaves, lax to spiciform inflorescences, and solitary or paired spikelets subtended by one to several setae. The spikelets in Setaria are obovoid to long-ellipsoid, glabrous, with the lower glume usually one-half the length of the spikelet or shorter, the upper glume and lower lemma subequal, the lower palea as long as the upper anthecium to reduced or absent, the lower flower absent or present and then staminate, and the upper anthecium indurate and smooth to transversely rugose. Base chromosome number in the genus is x = 9. A key to all 66 Setaria species occurring in the Old World is presented, followed by morphological descriptions, synonymy, typifications, distribution maps, notes, and illustrations of selected species. Two new combinations are proposed: Setaria desertorum (A. Richard) Morrone and Setaria obtusifolia (Delile) Morrone.